Influence of Socio Economic Factors on HIV /AIDs Treament Adherence Among Patients in a Hospital Setting : Case Study of Mukono General Hospital in Mukono Central Division. - Kenyangi Allen (Uganda Christian University, 2024)
The treatment of HIV/AIDS patients in a hospital environment was based on three objectives, which include: to establish the effect of social support networks on HIV/AIDS treatment adherence among patients at Mukono General Hospital and to establish the effect of employment status on HIV/AIDS treatment adherence among patients at Mukono General Hospital to examine the effect of This research report was undertaken to investigate the influence of socio economic factors on healthcare accessibility on HIV/AIDS treatment adherence among patients at Mukono General Hospital. The researcher used a sample size of 63 respondents and used questionnaires and interview guide to collect data and later the data was analyzed using the statistical package for social sciences (SPSS). Results of the first objective showed that social support networks have a significant effect on HIV/AIDS treatment adherence among patients at Mukono General Hospital. Supported by the following responses; 54% of the respondents were positive to the statement that social support serves as a buffer against the psychological stressors associated with HIV/AIDS and medication side effects, thereby enhancing patients' ability to adhere to treatment protocols; 62% were positive to the statement that social support networks provide emotional encouragement, practical assistance, and positive reinforcement, all of which are essential for patients to adhere to their treatment regimens. Results of the second objective revealed that employment status has a significant effect on HIV/AIDS treatment adherence among patients at Mukono General Hospital. Supported by the following responses; 56% of the respondents were positive to the statement that employment can provide financial stability, access to healthcare benefits, and structure to daily routines, all of which positively influence treatment adherence in HIV/AIDS patients. Results of the third objective showed that healthcare accessibility has a significant effect on HIV/AIDS treatment adherence among patients at Mukono General Hospital. 51% had a positive response to the statement that limited access to healthcare facilities and long waiting times negatively affect treatment adherence among individuals living with HIV/AIDS. There is need for Mukono General Hospital to reducing geographical, financial, and social barriers to care. Expanding the availability of healthcare facilities in underserved areas, offering mobile health clinics, and integrating telemedicine services can ensure patients receive consistent care regardless of their location